HIGH JUMP DEVELOPMENT OF SPORTS SCHOOL STUDENTS IN VOLLEYBALL TRAINING - Khushmurodov , Bekzod Abduraimovich (Innovative Development in Educational Activities, 2023)
This article discusses the problems of developing the qualities of jumping and jump endurance of volleyball players of children and youth sports schools.